FAKTOR? FAKTOR YANG MEMPENGARUHI MINAT MENGIKUTI PROGRAM PENDIDIKAN BREVET PAJAK DI STIE PERBANAS SURABAYA - Bayu Sarjono (The Indonesian Accounting Review, 2011)
Tax certification of Education Progam is estabilished by STIE Perbanas Surabaya in the form of training for university students or external party. At this moment, the demand for a tax occountant or tax consultant keeps on increasing, moreover when the there is Law No. 28 Year 2007 about Taxation General Stipulation. This condition has the effect of effort performed by DJP in order to increase state revenue. Universities are expected produce the graduates with enough knowledge and skill of taxation. Tax certification training is expected to support the graduates' competency. This research tries  to find  out what factors those influence university students to be interested in joining the tax ceitification program at STIE Perbanas Surabaya. This research is quantitative research using multiple regression test. The respondents in this research consist of all members of tax certification of Level I and Level II. The data were collected by spreading direct questionnaires and performingFocus Group Discussion. The result of statistic test shows that only economic motivation variable has significant infiuence towards the interest to join tax certification program. They explain that they join the tax certification program in order to get ligal document that can be used to apply for a job and also because they think that they don iow any intention to become tax accountont or tax consultant.